Microfluidic channel integrated with a lattice lightsheet microscopic system for continuous cell imaging. Issue 2 (9th December 2020) - Fan, Yu-Jui; Hsieh, Han-Yun; Tsai, Sheng-Fang; Wu, Cheng-Hsuan; Lee, Chia-Ming; Liu, Yen-Ting; Lu, Chieh-Han; Chang, Shu-Wei; Chen, Bi-Chang
Abstract : In this study, a continuous cell-imaging system with subcellular resolution was developed by integrating a microfluidic platform with lattice lightsheet microscopy (LLSM). Abstract : In this study, a continuous cell-imaging system with subcellular resolution was developed by integrating a microfluidic platform with lattice lightsheet microscopy (LLSM). To reduce aberrations of the lightsheet propagating into the device, a microfluidic channel sealed with a water refractive index-matched thin film was fabricated. When the lightsheet emerged from the water-immersed objectives and penetrated through the water refractive-matched thin film into the microfluidic channel at an incident angle, less light scattering and fewer aberrations were found. Suspended cells flowed across the lattice lightsheet, and an imaging system with the image plane perpendicular to the lightsheet was used to sequentially acquire cell images. By applying a thinner lattice lightsheet, higher-resolution, higher-contrast images were obtained. Furthermore, three-dimensional cell images could be achieved by reconstructing sequential two-dimensional cell images.